Analysing John Mearsheimer's Idea of Offensive Realism in a Changing World Order: Examining the Resilience of Offensive Realism in the Context of a Shifting Global Order (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Hans Morgenthau's introduction of realism as a framework for the study of internationalaffairs was almost fifty years ago. Not only has the strategy survived a sustained onslaught from noninternalsources like liberal institutionalism, the democratic peace school, and constructivism, but it hasalso endured a clearly polarizing trend from its inception. There are now several subgroups, eachbrandishing a different adverb to distinguish itself and announce a different focus or variety. An ascendantChina in Northeast Asia is the most worrisome prospect for the United States in the early twenty-firstcentury. Whether or whether China's economy maintains its fast rate of modernization is crucial to thecountry's chances of becoming a prospective hegemon. The Soviet Union during the Cold War presenteda compelling basis for a robust and cohesive Atlantic Alliance. Beyond its own safety, Western Europe'sdestiny was the United States' primary geopolitical priority throughout the Cold War